Structure and dielectric properties of (Na0.50Bi 0.50)1-xBaxTiO3: 0≤x≤0.10 - Ranjan R.; Dviwedi A. (My University, 2025)
Solid solution of (1-x)Na0.5Bi0.5TiO 3-xBaTiO3 is investigated in the composition range 0.00≤x≤0.10. It is shown that the system exhibits rhombohedral structure up to x=0.055 and then becomes 'nearly cubic' for x≥0.06. Temperature dependent dielectric measurements reveals three peaks in the imaginary part of the dielectric constant for compositions exhibiting rhombohedral as well as 'nearly cubic' structures. The first of these three peaks exhibits Vogel-Fulcher type relaxation behaviour. © 2005 Elsevier Ltd. All rights reserved.